1977
DOI: 10.1111/j.1365-2621.1977.tb12663.x
|View full text |Cite
|
Sign up to set email alerts
|

VARIATION IN INHIBITION OF C. botulinum BY NITRITE IN PERISHABLE CANNED COMMINUTED CURED MEAT

Abstract: A series of seven tests was conducted to establish a base line for the inhibition of C. borulinum by nitrite in a perishable canned meat product. The product was subjected to abusive storage at 27°C. The degree of variation in swell times and rates among the tests was determined. Predicted average times to first swell were 6.7, 29.8, 82.6 and 94.3 days when 0, 50, 100 and 156 rig/g of sodium nitrite was added to the meat. The primary effect of nitrite appears to have been in determining the length of the lag p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1978
1978
1984
1984

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Inoculum. The C. botulinum inoculum consisted of a mixture of five type A and five type B strains prepared as described earlier (6). The mixed spore suspension was heated at 80°C for 15 min and added to the meat during formulation, using a target level of 100 spores/g of product.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inoculum. The C. botulinum inoculum consisted of a mixture of five type A and five type B strains prepared as described earlier (6). The mixed spore suspension was heated at 80°C for 15 min and added to the meat during formulation, using a target level of 100 spores/g of product.…”
Section: Methodsmentioning
confidence: 99%
“…It was earlier reported that some variation occurred among inoculated packs of perishable canned comminuted cured meat (6). Tests have been conducted to determine the cause of this variation, thereby improving the test system for monitoring additives.…”
mentioning
confidence: 99%
“…botulinum which survive pasteurization, and experiments sufficiently large to study most of these factors demand relatively large quantities of bacteriological media or pork. Although bacteriological media can be standardized, at least within a manufactured batch, similar experience using pork as a growth medium is generally lacking, but there have been several reports that experimental variation could be attributed to differences between batches of pork (Rhodes & Jarvis, 1976) even in meat formulations (Tompkin, Christiansen & Shaparis, 1977;Sofos et al , 1979).…”
Section: Introductionmentioning
confidence: 98%
“…hotulinum in pork slurries or pork products. Tompkin, Christiansen & Shaparis (1978a) stated that fat content did not influence botulinal inhibition in their canned, comminuted pork product but offered no supporting data. Fat levels of ca.…”
mentioning
confidence: 97%
See 1 more Smart Citation